Pengelolaan Supervisi Akademik Di SMP Negeri 2 Tasikmadu Karanganyar - Widarto, Widarto; , Prof. Dr. Sutama, M.Pd (2015)
The general objective of this study describes the management of academic supervision in SMP Negeri 2 Tasikmadu Karanganyar. While the specific purpose of this study is to describe about 1) Planning academic supervision; 2) Implementation of academic supervision; and 3) assessment and feedback of academic supervision in SMP Negeri 2 Tasikmadu Karanganyar. This type of research is qualitative. The research approach uses phenomenology. Subjects were principals and teachers. Methods of data collection using in-depth interviews, observation and documentation. Data were analyzed using triangulation. Results of the study are: 1) Planning of academic supervision in SMP Negeri 2 Tasikmadu Karanganyar compiled based on units of time semesters, each semester of at least one academic supervision; 2) Implementation of academic supervision in SMP Negeri 2 Tasikmadu Karanganyar adapted to ongoing learning material that is taught by each teacher takes place each semester one time; and 3) Assessment of academic supervision in SMP Negeri 2 Tasikmadu Karanganyar carried out based on the implementation of the supervision of classroom visits by principal. Feedback of academic supervision in SMP Negeri 2 Tasikmadu Karanganyar take place between principals and teachers in the form of reflection result academic supervision, the school principal to provide input to the teacher about some things that need to be fixed such as the allocation of instructional time, tools and instructional media. Keyword : academic, management, supervision